Simian herpesviruses and their risk to humans - Estep, Ryan D. (2010)
A high level of genetic and physiological homology with humans has rendered non-human primates (NHP) an essential animal model for biomedical research. As such NHP offer a unique opportunity to study host-pathogen interactions in a species that closely mimics human biology but can yet be maintained under tight laboratory conditions. Indeed, studies using NHP have been critical to our understanding of pathogenesis as well as the development of vaccines and therapeutics. This further facilitated by the fact that NHPs are susceptible to a variety of pathogens that bear significant homology to human pathogens. Unfortunately, these same viruses pose a potential health issue to humans. In this review we discuss the simian herpesviruses and their potential to cause disease in researchers that come into close contact with them.